Mesostructure engineering in additive manufacturing of alloys - Wei, Siyuan (2023)
While there is considerable interest in additive manufacturing of alloys and their resulting properties, the ‘bottom up’ approach of fabricating components—point by point, line by line, and layer by layer, offers a new tool for micro- and meso‑ structure control that has not yet been fully exploited by alloy designers. The mesostructures, which can be manipulated either through the choice of the processing parameters when prealloyed powders are used, or by using mixed powders (‘in situ alloying’), can be used to improve the overall mechanical performance of the printed part. Whilst the microstructures can be tailored to enhance strength, the mesostructures can be designed to improve the fracture toughness and other damage tolerance properties. These aspects are highlighted in this viewpoint paper.